2020
DOI: 10.1002/adfm.202008300
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Electron Transport Materials in Perovskite Solar Cells

Abstract: In the past decade, the perovskite solar cell (PSC) has attracted tremendous attention thanks to the substantial efforts in improving the power conversion efficiency from 3.8% to 25.5% for single‐junction devices and even perovskite‐silicon tandems have reached 29.15%. This is a result of improvement in composition, solvent, interface, and dimensionality engineering. Furthermore, the long‐term stability of PSCs has also been significantly improved. Such rapid developments have made PSCs a competitive candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 208 publications
(250 reference statements)
0
122
0
Order By: Relevance
“…Up to now, the high performance of PSCs is mainly based on a planar or mesoporous structure [10][11][12][13][14]. In these architectures, the electron transport layer (ETL) as the bottom layer is the key in the device fabrication toward high efficiency and long-term stability [15]. Tin dioxide (SnO 2 ) has been demonstrated as an efficient ETL candidate in the case of PSCs due to its excellent mobility, high light transmittance and suitable energy level alignments with perovskites [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the high performance of PSCs is mainly based on a planar or mesoporous structure [10][11][12][13][14]. In these architectures, the electron transport layer (ETL) as the bottom layer is the key in the device fabrication toward high efficiency and long-term stability [15]. Tin dioxide (SnO 2 ) has been demonstrated as an efficient ETL candidate in the case of PSCs due to its excellent mobility, high light transmittance and suitable energy level alignments with perovskites [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have continuously worked on finding inorganic alternatives to boost higher PCE and stability with lower cost. Compared with organic top ETL, inorganic top ETL has the advantages of (a) facile fabrication process, 50,64,168,[202][203][204][205] (b) high intrinsic stability, 3,4,18,32,50,[206][207][208][209] (c) easily adjustable optical and electronic properties, 3,28,34,35,42,153,159,208 (d) low-temperature or no post-treatment, 26,41,50,155,168,190,203 (e) low cost, 68,163,187,210,211 (f) additional function as passivate layer. 7,36,175 All the advantages of inorganic top ETL accelerate its application in high-performance inverted PSCs.…”
Section: Principles Of Top Etlmentioning
confidence: 99%
“…5), are usually preferred as ETL materials, with each material having specific advantages to boost the PCE. [37][38][39] Among the reported metal oxides, TiO2 is an ETL material that has been most widely used by various research groups. However, Leijtens et al reported lower stability of PSC devices with the use of TiO2 (due to its high photocatalytic activity under UV light) as an ETL material when compared with a TiO2-free PSC.…”
Section: Organic Electron Transport Layer Materialsmentioning
confidence: 99%
“…For example, the most commonly used HTLs used in PSCs are Spiro-OMeTAD, 48 PTAA, 49 PEDOT:PSS 50 and nickel oxide (NiO). 51 Similarly, a variety of materials have been used as ETLs, including metal halides and oxides, [52][53][54][55] organic small molecules, 56 conjugated polymers, 57 and non-conjugated polymers. 58 These layers are often sandwiched between the electrodes and the perovskite layer, and their main function is to facilitate efficient charge extraction while reducing carrier recombination.…”
Section: Organic Electron Transport Layer Materialsmentioning
confidence: 99%